Sustainability and food and nutrition security. A vulnerability assessment framework for the Mediterranean Region - Prosperi, P.; Allen, T.; Padilla, M.; Peri, I.; Cogill, Bruce (SAGE Publications, 2014)
Recurrent food crises and climate change, along with habitat loss and micronutrient deficiencies, are global issues of critical importance that have pushed food security and environmental sustainability to the top of the political agenda. Analyses of the dynamic linkages between food consumption patterns and environmental concerns have recently received considerable attention from the international and scientific community. Using the lens of a broad sustainability approach, this conceptual article aims at developing a multidimensional framework to evaluate the sustainability of food systems and diets, applicable to countries of the Mediterranean region. Derived from natural disaster and sustainability sciences, a vulnerability approach, enhanced by inputs from the resilience literature, has been adapted to analyze the main issues related to food and nutrition security. Through causal factor analysis, the resulting conceptual framework improves the design of information systems or metrics assessing the interrelated environmental, economic, social, and health dynamics of food systems.